2005
DOI: 10.1074/jbc.m508623200
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid Fibril Formation of α-Synuclein Is Accelerated by Preformed Amyloid Seeds of Other Proteins

Abstract: ␣-Synuclein is one of the causative proteins of familial Parkinson disease, which is characterized by neuronal inclusions named Lewy bodies. Lewy bodies include not only ␣-synuclein but also aggregates of other proteins. This fact raises a question as to whether the formation of ␣-synuclein amyloid fibrils in Lewy bodies may occur via interaction with fibrils derived from different proteins. To probe this hypothesis, we investigated in vitro fibril formation of human ␣-synuclein in the presence of preformed fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 69 publications
5
98
1
Order By: Relevance
“…Once the nucleus is formed, subsequent polymerization proceeds rapidly through the sequential incorporation of precursor molecules into the nucleated fibrils. Many experiments have demonstrated that fibrillation from various proteins involves a lag period that corresponds to the nucleation process before the formation of mature, welldefined amyloid fibrils (Lomakin et al 1996;Naiki et al 1997;Yagi et al 2005;Hamley 2007;Sasahara et al 2008;Xue et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Once the nucleus is formed, subsequent polymerization proceeds rapidly through the sequential incorporation of precursor molecules into the nucleated fibrils. Many experiments have demonstrated that fibrillation from various proteins involves a lag period that corresponds to the nucleation process before the formation of mature, welldefined amyloid fibrils (Lomakin et al 1996;Naiki et al 1997;Yagi et al 2005;Hamley 2007;Sasahara et al 2008;Xue et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of aS fibrillation can be increased by abolishing the rate-limiting nucleation step through the addition of preformed fibrils (seeds) to the aggregating solution, which act as nuclei for monomer accretion and fibril growth (32). Because DOPAL oxidation products (essentially DOPAL-quinone, referred to here as DPQ) also strongly quench ThT fluorescence, aS fibrillation in the presence of DOPAL cannot be properly evaluated by using ThT (31) unless DOPAL oxidation is inhibited (see below).…”
Section: Dopal Induces the Formation Of Fibril-incompetent Soluble Olmentioning
confidence: 99%
“…21,22 Given the off-pathway nature of DSOs and their tendency to self-propagate to nonfibrillar aggregates, it is important to understand whether DSOs can cross-propagate nonfibrillar aggregates of Ab. In order to investigate this, monomeric Ab42 (15 mM in 20 mM Tris, 50 mM NaCl, 0.01% NaN 3 at pH 8.0) was incubated with 6.7% (molar percent, 1 lM) DSO at 37 C under quiescent conditions.…”
Section: Dsos Can Cross-propagate Soluble Aggregates Of Abmentioning
confidence: 99%